Novel lipid mediators in resolution of inflammation - Serhan, Charles (Henry Stewart Talks, 2009)
Complete resolution of the acute inflammatory response and its return to homeostasis is essential, Efforts to identify and characterize the cellular and molecular mechanisms that govern resolution of self-limited inflammation, Systems approach with temporal analysis of the evolving inflammatory exudates using unbiased mediator lipidomics/informatics, proteomics, and cellular traffic with murine resolving exudates, Novel endogenous pathways of local acting mediators that are dual acting, and that are both anti-inflammatory and pro-resolving, Biosynthesis and actions of "resolvins" and "protectins", E-series resolvins and D-series resolvins, Actions of neuroprotectin D-1, Biosynthesis of aspirin-triggered lipid mediators and their impact in regulating acute inflammatory responses, The resolution of acute inflammation is an active process that can be accelerated
Reviewed at 2020/05/01